2017
DOI: 10.1016/j.jds.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endodontic sealers on bond strength of restorative systems to primary tooth pulp chamber

Abstract: Background/purpose Although current literature suggests that root canal sealers affect the bonding ability of restorative systems to pulp chamber dentin of permanent teeth, primary teeth have not been investigated. This study intended to evaluate the microtensile bond strength (μTBS) of three restorative systems to pulp chamber dentin in primary teeth and to determine the effect of two different root canal sealers on the μTBS. Materials and methods Ninety primary molars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Our results showed that Metapex weakens the bonding adhesion. This reduction could be attributed to two main reasons that were also mentioned in other studies: remnant Metapex that directly affects the bonding and also dissolving of remnant Metapex material when exposed to adhesive primer, which contains ethanol and acetone [ 12 ].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Our results showed that Metapex weakens the bonding adhesion. This reduction could be attributed to two main reasons that were also mentioned in other studies: remnant Metapex that directly affects the bonding and also dissolving of remnant Metapex material when exposed to adhesive primer, which contains ethanol and acetone [ 12 ].…”
Section: Discussionmentioning
confidence: 82%
“…Hence, we evaluated the effect of different root canal filling materials and their solvents on shear bond strength of composite to anterior primary teeth. Although it was reported that root canal sealers affect bond strength of resin-based materials to pulp chamber dentin in permanent teeth [ 12 ], less attention has been given to this subject in primary dentition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature review, there are very few studies on root canal sealer and contaminated primary tooth bond strength. Elbay and Tosun found that composite materials bonded to pulp chamber dentin in primary teeth had higher strength than compomers and resin-modi ed glass ionomers in their study on bond strength of restorative systems in the primary tooth pulp chamber of endodontic sealers [20]. In addition, the composite was applied to primary teeth in their study.…”
Section: Discussionmentioning
confidence: 98%